KETERLIBATAN ORANGTUA PEMBELAJARAN DI RUMAH DIMASA PADA MADRASAH IBTIDAIYAH - Syaiful Anwar; Baharudin; Rifda El Fiah; Ida Fiteriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Parental engagement plays an important role in supporting children’s academic and emotional development. The emotional bond between parents and children serves as a fundamental basis for creating meaningful learning processes, particularly in home-based learning. This study aims to explore and analyze the processes and patterns of parental engagement in supporting children’s learning at home from a social capital perspective. The study employs social capital theory as an analytical framework and adopts a qualitative approach using a case study design. The research was conducted in six Islamic elementary schools (Madrasah Ibtidaiyah), namely, MIN 1 and MIN 5 in South Lampung Regency,. Data were collected through in-depth interviews, observations, and document analysis. Data analysis followed the interactive model proposed by Miles and Huberman. The findings reveal that parental engagement in home-based learning is manifested through five main processes: accompanying children during learning activities, providing emotional and academic support, supervising the learning process, providing learning facilities, and assisting children in overcoming learning difficulties. These findings indicate that social capital, particularly within the family context, plays a significant role in sustaining home-based learning. This study provides empirical insights within the Indonesian context and recommends the development of a home-based social capital approach as an alternative analytical framework for future research on parental engagement in children’s education